Mitigating mass violence and managing threats in contemporary society - Crews, Gordon A.; Markey, Mary Ann; Kerr, Selina E. M. (Advances in psychology, mental health, and behavioral studies (APMHBS) book series, 2021)
"This edited book explores the shifting definitions and implications of mass violence and investigates the premise that the perpetrators' decision regarding their choice of weapon(s) to carry out their planned mass violence is based upon their accessibility to particular weapons. This leads to whether perpetrators of mass violence share similar goals and motivations for their sprees, as well as display commonalities in their direct and indirect warning behaviors"--